2D Synchrotron Radiation Interferometer for Measuring the Transverse Dimensions of an Electron Beam in a Circular Accelerator; Russian Physics Journal; Vol. 60, iss. 4 - Novokshonov A. I. Artem Igorevich (2017, 2017)
Title screen